Synthesis of a catalyst of Mn-Fe-O by mechano-chemical reaction - Barroso Quiroga, Maria Martha (2013)
In this work, the Fe–Mn–O system was mechanically processed in a high-energy ball-milling. The as milled powders were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS) and specific surface area measurement. Catalytic total oxidation of n-hexane was studied to find out the suitability of the material for VOC decomposition reaction. The route of the solid state transformation of Mn–Fe–O system has been established as a function of the cumulated energy from mechanical milling. Complex multicomponent catalysts, which may be difficult to prepare by conventional high temperature treatment, have been successfully prepared by milling.